Dispute settlement in the UN Convention on the Law of the Sea - Klein, Natalie (Natalie S.) (Cambridge studies in international and comparative law (Cambridge, England : 1996) ;, 2005)
The UN Convention on the Law of the Sea is one of the most important constitutive instruments in international law. This book explores whether a compulsory dispute settlement mechanism is necessary for the regulation of the oceans under the Convention.